1993
DOI: 10.1001/jama.1993.03500080052031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lodophor vs Iodine Tincture Skin Preparation on Blood Culture Contamination Rate

Abstract: The effectiveness of the skin antiseptic may be an important factor in determining contamination rate in blood culturing. If these results are confirmed by others, then institutions that have a high blood culture contamination rate when using an iodophor for skin preparation should consider changing to iodine tincture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 9 publications
1
39
1
Order By: Relevance
“…Our estimation of bacterial contamination rates of blood donations is higher than those previously reported in whole‐blood units, but consistent with those of the first few ml collected [20] and with blood‐culture contamination rates reported in clinical settings, where the same mechanisms may be implicated [21,22].…”
Section: Discussionsupporting
confidence: 90%
“…Our estimation of bacterial contamination rates of blood donations is higher than those previously reported in whole‐blood units, but consistent with those of the first few ml collected [20] and with blood‐culture contamination rates reported in clinical settings, where the same mechanisms may be implicated [21,22].…”
Section: Discussionsupporting
confidence: 90%
“…The total blood culture contamination rate in National Hospital Abuja was found to be 10.4%, far above the benchmark of 2-3% 7,9,10,11,12. Contamination was relatively more in paediatric patients than in adults, with a total culture per contaminant yield of 9 against 13, and rate of 11% against 8%.…”
Section: Discussionmentioning
confidence: 80%
“…The acceptable blood contamination rate benchmark is 2-3%,7,9,10,11,12 with rates ranging from 1% to 9% 13. Factors associated with blood culture contamination include, but are not limited to, poor technique and procedure used to collect blood, lack of dedicated phlebotomists,8,9,14 improper skin antisepsis 15,16,17.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that drawing blood cultures from young uncooperative children may influence the rate of contamination 14. A contamination rate of 2% to 3% has been considered acceptable 15. These false positive or contaminant blood cultures may lead to unnecessary diagnostic evaluation and treatment and prolonged hospitalization 1618.…”
Section: Discussionmentioning
confidence: 99%